Reproductive hormones profiles in Malnad Gidda cows during estrous cycle - K, HEMANTH GOWDA; SWAMY, M NARAYANA; B, SRIDHAR N (The Indian Journal of Animal Sciences, 2022)
Malnad Gidda cows are famous for regular calving under low input regime. However, Malnad Gidda cattle are poorly studied with regard to their reproductive efficiency. The present study was undertaken to establish the baseline values for reproductive hormones in Malnad Gidda cows. Malnad Gidda cows (6) aged between three to four years were selected. Upon confirming the regular estrous cycles, blood was collected on the day of estrus (day 0) and the day 3, 6, 9, 12, 15, 18, 20 of estrous cycle and subsequent estrus (day 0). Serum was separated by centrifugation at 3,000 rpm at 30°C for 20 min and stored at -20°C until analyzed. 17β-estradiol and progesterone concentration in serum was measured using commercial radioimmunoassay (RIA) kit (BRIT, Mumbai). The serum 17β-estradiol hormone concentration showed a significant decrease from day 0 to day 3. Later, the concentration increased significantly up to day 6 and then decreased by day 9. The concentration of estradiol showed significantly increasing trend from day 12 and onwards up to day 20. The concentration of progesterone increased significantly from day 3 to day 9. Thereafter, the concentration decreased significantly from day 12 to day 20. The present study revealed the normal functioning of the Hypothalamo-Pituitary-Ovarian relationship axis which is responsible for normal estrous cycles in Malnad Gidda cows. The peak progesterone level was observed from 9th to 12th day and on the same days, the estradiol level was at its lowest levels.